Dural Puncture Epidural for Labor Analgesia: Is It Really an Improvement Over Conventional Labor Epidural Analgesia?. Issue 1 (22nd March 2023) - Segal, S.; Pan, P.H.
Abstract : ( Anesthesiology . 2022;136:667–669) Continued innovations of the standard epidural technique have allowed for improvement of the quality of analgesia experienced by laboring women. The introduction of conventional neuraxial analgesia offered effective and safe pain relief to parturients, with relatively infrequent adverse outcomes, and is utilized in >73% of contemporary births in the United States. Procedural refinements over time have offered improvement in analgesia quality, including continuous local anesthetic infusions, optimizations of volume and concentrations of medications delivered, the addition of opioids to the injectate, timed bolus injections, and patient-controlled epidural analgesia. As protocol variations, both combined spinal-epidural and dural puncture epidural utilize a smaller spinal needle that is passed through the epidural needle. In combined spinal-epidural, small doses of opioid and local anesthetic are injected into the intrathecal (IT) space. With dural puncture epidural, the spinal needle is used to intentionally puncture the dura, but no drugs are injected. Initial evidence suggested improved analgesia with this technique over standard epidural and combined spinal-epidural, but the literature has produced mixed results since. In the same issue of this journal, Tan et al deliver results from a randomized clinical trial of obese parturients receiving dural puncture epidural vs conventional epidural to determine if analgesia quality is enhanced by dural puncture in this population at higher risk for epidural failure.